UML-based behavior specification of interactive multimedia applications / Johann Ashaary - Ashaary, Johann (2004)
Multimedia applications are becoming more and more popular as we speak, especially in the entertainment industry where there are multimedia games, websites which is made with Flash and also for educational purposes such as e-textbooks which can be found in a cd-rom. But developing a multimedia application is usually an ad-hoc process where there is no modelling technique implemented. Programs are made up along the development process, and all the visualization of the end product are kept in the heads of the developer. This would cause the end product to be functional but not effective. A solution is to have an analysis phase for the construction of the multimedia application where modelling is done before constructing it. By using the UML as the modelling language and adding two more model to it which is the presentational and navigational model, the modelling of interactive multimedia applications can be done effectively to create a product with no defects.